Clinical Problem solving : How much oxygen is in the blood? PaO2, SaO2 and Oxygen Content - Lawrence Martin; Satish Deopujari; Vishram Buche; Nilesh Darvhekar (Wolters Kluwer Medknow Publications, 2018)
In the field of blood gas interpretation, confusion about PaO2, SaO2 and oxygen content is second only to confusion about mixed acid-base disturbances. This article attempts to clear the concepts of PaO2, SaO2 and Oxygen Content to answer the question of "How much oxygen is in the blood?" with clinical problem solving.